2019
DOI: 10.1007/s00421-018-04063-9
|View full text |Cite
|
Sign up to set email alerts
|

An acute dose of inorganic dietary nitrate does not improve high-intensity, intermittent exercise performance in temperate or hot and humid conditions

Abstract: Purpose Dietary nitrate (NO 3 − ) has repeatedly been shown to improve endurance and intermittent, high-intensity events in temperate conditions. However, the ergogenic effects of dietary NO 3 − on intermittent exercise performance in hot conditions have yet to be investigated. Methods In a randomised, counterbalanced, double-blind crossover study, 12 recreationally trained males ingeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 57 publications
0
46
0
Order By: Relevance
“…Data extraction was then independently performed by the same three authors. Specifically, study design, sample size, subject characteristics, form, dose, and duration of NO 3 − supplementation, placebo characteristics, experimental procedures, and testing conditions were obtained from the text of eligible papers [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Effect sizes (ES), i.e., Hedge's g, for NO 3 − -induced changes in peak or maximal power were calculated from either 1) the means and SDs for the NO 3 − and placebo trials along with the exact P values for the within-subject comparison [49,53,55,58,60], or 2) anonymized individual subject data obtained from the authors [42-48, 50-52, 54, 56, 57, 59].…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data extraction was then independently performed by the same three authors. Specifically, study design, sample size, subject characteristics, form, dose, and duration of NO 3 − supplementation, placebo characteristics, experimental procedures, and testing conditions were obtained from the text of eligible papers [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Effect sizes (ES), i.e., Hedge's g, for NO 3 − -induced changes in peak or maximal power were calculated from either 1) the means and SDs for the NO 3 − and placebo trials along with the exact P values for the within-subject comparison [49,53,55,58,60], or 2) anonymized individual subject data obtained from the authors [42-48, 50-52, 54, 56, 57, 59].…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Since data from the 12 subjects in our original study [43] were also included in a subsequent report [50], only the results from the eight additional subjects in the latter study were used in the meta-analysis. A number of the studies employed a repeated sprint cycling protocol and/ or only reported the mean power during a Wingate-style test [51,52,54,55,60]. In such instances, peak power from the first sprint was obtained from the authors and utilized in the meta-analysis.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…There is also evidence that acute BJ ingestion can improve all-out sprint performance. 17 Although NO 3 − supplementation appears to preferentially enhance contractile function in mouse fast-twitch skeletal muscle via improved skeletal muscle calcium (Ca 2+ ) handling, 18 NO 3 − supplementation studies in humans have reported improved force production in the absence of alterations to skeletal muscle Ca 2+ handling proteins 10 and the magnitude of improvement in evoked force in human mixed fibre whole muscle [8][9][10] has been lower than mouse fast-twitch muscle. 18 It has been suggested that recruitment of fast-twitch skeletal muscle might be greater during eccentric muscle contractions (ECC).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study from Kent et al (2019), no improvement in repeated sprint performance was found in hypoxia after BRJ consumption (Kent et al 2019). A study performed by Smith et al (2019) concluded that BRJ does not improve high-intensity intermittent exercise performance in different temperatures (temperate, hot and humid) (Smith et al 2019). Isometric midthigh pulls peak force was significantly higher after BRJ consumption in adolescent males (Bender et al 2018).…”
Section: Recreationally Active Menmentioning
confidence: 94%